If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63x + 9 = -36 Reorder the terms: 9 + 63x = -36 Solving 9 + 63x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 63x = -36 + -9 Combine like terms: 9 + -9 = 0 0 + 63x = -36 + -9 63x = -36 + -9 Combine like terms: -36 + -9 = -45 63x = -45 Divide each side by '63'. x = -0.7142857143 Simplifying x = -0.7142857143
| (6/7)*v=42 | | 105=23x+1+11x+2 | | 20x^4-20x^2+3=0 | | 5u+5=-10 | | 3x+5y=-67 | | 4+5m=12+3m | | 12x^3-12x^2+8=0 | | (X/15)=15 | | x+70+75+x+45=180 | | 2(x-4)=3x+32 | | 20a+13b+6c+6c-6b-4a= | | -3x-y=26 | | (y^1/8)=-1 | | 63x+9=36 | | 2t-11=15 | | -3x+3y=30 | | 15x-3=8x+16+44 | | cotg4x/cotg3x | | 8u=4v-34 | | 4x+-2y=24 | | -4x+y=-27 | | 8x=6x-10+30 | | 8x/3-8=8 | | 4h+9=33 | | 7u+5=2u-10 | | 4(x-4)+1=4x-14 | | (4/3)/(5/4) | | 10(z+4)-4(z-2)=2(z-3)+3(z-1) | | 2(4X-11)=2 | | -5x+5y=-25 | | x^2+x^2=57 | | 4=-3(24-y)+2(y-2) |